1995
DOI: 10.1016/0014-5793(95)00153-z
|View full text |Cite
|
Sign up to set email alerts
|

Wortmannin, a specific inhibitor of phosphatidylinositol‐3 kinase, blocks osteoclastic bone resorption

Abstract: The biological role of phosphatidylinositol (PI)-3 kinase was examined in osteoclast-like multinucleated cells (OCLs) formed in co-cultures of mouse osteoblastic ceils and bone marrow cells. The expression of PI-3 kinase in OCLs was confirmed by Western blot analysis. Wortmannin (WT), a specific inhibitor of PI-3 kinase, inhibited PI-3 kinase activity in OCLs both in vitro and in vivo. WT also inhibited pit-forming activity on dentine slices and disrupted a ringed structure of F-actin-containing dots (an actin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
0
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 142 publications
(84 citation statements)
references
References 27 publications
2
80
0
2
Order By: Relevance
“…The sealing zones serve to attach osteoclasts to the bone surface and isolate the resorption areas from the surrounding areas (Chambers and Magnus 1982;Väänänen et al 2000). It has been reported that disruption of the sealing zones suppresses the boneresorbing activities of osteoclasts (Lakkakorpi and Väänänen 2004;Nakamura et al 1991;Suzuki et al 1996). In the present study, we have demonstrated that luteolin inhibits osteoclastic bone resorption.…”
Section: Discussionsupporting
confidence: 70%
“…The sealing zones serve to attach osteoclasts to the bone surface and isolate the resorption areas from the surrounding areas (Chambers and Magnus 1982;Väänänen et al 2000). It has been reported that disruption of the sealing zones suppresses the boneresorbing activities of osteoclasts (Lakkakorpi and Väänänen 2004;Nakamura et al 1991;Suzuki et al 1996). In the present study, we have demonstrated that luteolin inhibits osteoclastic bone resorption.…”
Section: Discussionsupporting
confidence: 70%
“…(21)(22)(23) However, the in vivo data indicated a normal number of osteoclasts in Pik3r1 DOc/À Pik3r2 À/À mice, and the formation of TRAP-positive osteoclasts from Pik3r1 DOc/À Pik3r2 À/À cells was comparable to control cells in vitro. Our results suggest that class IA PI3K is dispensable for the differentiation and survival of osteoclasts, and indicate that other PI3Ks sensitive to the PI3K inhibitors evidently play a redundant role.…”
Section: Discussionmentioning
confidence: 84%
“…(14,15) PI3K is known to be stimulated by M-CSF and integrin a v b 3 , both of which are crucial for osteoclast function. (8,9) In vitro inhibitor experiments suggest that PI3K is involved in the differentiation (21) and the bone-resorbing activity (22,23) of osteoclasts, but the level of PI-3,4,5-P 3 has not been quantitated in osteoclasts, and the in vivo function of PI3K in osteoclasts has also not been elucidated. In addition, because the PI3K inhibitors such as wortmannin and LY294002 suppress the catalytic activity of all classes of the PI3Ks, (16,24) the role of each PI3K class needs to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Osteoclastic cells were prepared as described previously (Nakamura et al, 1995). Briefly, osteoblastic cells were isolated from the calvariae of 2-day-old newborn ddYstrain mice and cultured on type I collagen gel.…”
Section: Materials and Methods Cell Culture Systemmentioning
confidence: 99%